Metaphor-based metaheuristics, a call for action: the elephant in the room - Aranha, Claus; Camacho Villalón, Christian L.; Campelo, Felipe; Dorigo, Marco; Ruiz, Rubén; Sevaux, Marc; Sörensen, Kenneth; Stützle, Thomas (Swarm intelligence, 2022)
Taking inspiration from natural behaviors to devise new optimization algorithms has played an important role in the history of the field of metaheuristics (Sörensen et al. 2017). Unfortunately, in the last two decades we have been witnessing a new trend by which dozens of metaphor-based metaheuristics based on the most diverse possible set of natural, artificial, social, and sometimes even supernatural phenomena and behaviors are proposed, without a clear motivation beyond the desire of their authors to publish their papers.